Perbandingan Penggunaan Media Cair Ekstrak Kedelai (Glycine max), Kacang Tanah (Arachis hypogaea L.), dan Kacang Hijau (Vigna radiata L) dalam Perbanyakan Pseudomonas fluorescens sebagai Agen Hayati - Ningsih, Fitria; Hefdiyah, Hefdiyah; Cahyo Pitoyo, Alief (Program Studi Biologi Fakultas Matematika dan IPA Universitas Annuqayah, 2024)
Pseudomonas fluorescens is one of the antagonist bacteria because it has the ability to induce systemic resistance. P. fluorescens has also been reported to increase the content of phenolic compounds in plants. These bacterium are widely used as biological agents for fungi, pathogenic bacteria and viruses in plants. The research method used in this research is the TPC method. The average number of P. fluorescens bacterial colonies obtained on each of the soybean, peanut and mung bean extract media was 1,68 x 108 CFU/ml, 4,44 x 108 CFU/ml and 6,08 x 108 CFU/ml. The purpose of this study was to determine which media was more effective against P. florescens bacteria in its growth on liquid extracts of soybean, peanut, and mung bean. The results indicate that the most effective media for the growth of P. fluorescens bacteria was the liquid media of mung bean extract, with an average total colony count of 6,08 x 108 CFU/ml.